PENGARUH PEMBERIAN TUGAS BESAR (TUGAS AKHIR) TERHADAP TINGKAT MOTIVASI BELAJAR MAHASISWA PENDIDIKAN TEKNIK BANGUNAN ANGKATAN 2022 - Riski Putri Santika (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to analyze the effect of large assignments on the level of learning motivation of building engineering education students class of 2022. This study uses a quantitative research design with explanation and with the Generalized Framework for Observational Research Methods (G-from) method . The population of this study were all Jakarta State University Building Engineering Education students who had taken the Steel Structure 1 course in 2023, and the research sample was 30 students who were randomly selected. The results showed that there was a positive effect of giving large assignments on the level of student learning motivation. The effect is moderated by several factors, namely the type of large assignment, the difficulty of large assignments, the availability of resources, and lecturer support.